Ocular Toxicity of Belantamab Mafodotin, an Oncological Perspective of Management in Relapsed and Refractory Multiple Myeloma - Wahab, Ahsan; Rafae, Abdul; Mushtaq, Kamran; Masood, Adeel; Ehsan, Hamid; Khakwani, Maria; Khan, Aqsa (Frontiers in Oncology, 2021)
Belantamab mafodotin (belamaf), an antibody-drug conjugate approved for the treatment of relapsed and refractory multiple myeloma (RRMM), is an anti B-cell maturation antigen (BCMA) agent. DREAMM-1, a first in-human trial of belamaf, reported several ocular toxicities requiring dose adjustments, dose delays and treatment discontinuations. In DREAMM-1, 53% of patients in part-1 and 63% of patients in part-2 had ocular toxicity. Similarly, 73% of patients in DREAMM-2 had keratopathy (71% in 2.5 mg/kg versus 75% in 3.4 mg/kg) with the most common symptoms being blurred vision and dry eyes. Ocular toxicity of belamaf is attributed to microtubule-disrupting monomethylauristatin-F (MMAF), a cytotoxic payload of the drug that causes an off-target damage to the corneal epithelial cells. Ocular adverse events (AEs) of belamaf are more frequent at higher doses compared with lower doses. Higher belamaf dose, history of dry eyes and soluble BCMA are associated with increased risk of corneal toxicity. Absence of ocular symptoms does not exclude the possibility of belamaf-induced ocular toxicity, so patients need slit lamp and Snellen visual acuity testing to detect microcytic-like epithelial changes and visual decline. Corticosteroid eyes drops for 4-7 days prior to belamaf dose do not prevent ocular AEs and may cause steroid-related AEs instead. Keratopathy and Visual Acuity scale (KVA) is recommended to document the severity of belamaf-induced ocular toxicity and make treatment adjustments. Management of toxicity includes dosage modifications, treatment interruption or discontinuations and preservative-free artificial tears along with close ophthalmology and hematology-oncology follow-ups.